ANALYSIS OF THE EFFECTS OF FINANCIAL DIMENSIONS AFFECTING BUSINESS PERFORMANCE ON CIVIC VIRTUE - VARIŞLI , Nuran; BAYAR , Münevver (SSD Journal, 2020)
Business performance can be associated with the progress of the financial system. Financial dimension is one of the most important administrative functions in a company. The financial dimension, which is responsible for planning and controlling the use of the organization's resources, affects all sectors of the enterprise as the operation of each sector depends on the budget. With the correct application of resources, operations can generate profits for the company. For a company to be successful, it is important to have an effective administrative structure in line with the goals and objectives of the business. The financial dimension accompanies the company's strategic planning and can show how resources should be used to achieve the set goals. The term of citizenship has historically been used to describe the human condition as a member of a society, as a right and duty holder, because of its social, cultural, political and economic content. Today, the concept of citizenship accepts a wider range of meanings and is also used to theoretically subsidize the concept of certain behaviors that spread in certain settings, such as organizational. The concept of organizational citizenship emphasizes that an organization involves a series of informal, individual and discretionary contributions that its participants can express or prevent without having to respond to sanctions or formal goals. Organizational citizenship refers to the fact that it tends to manifest to a lesser extent than personal interests. It should be noted that the dimension of citizenship most strongly impeded by this climate is precisely individual initiative. Civil virtue in terms of organizational citizenship serves to encourage a discourse of the public good. As virtue, the members of the organization are required not only in positions of respect and tolerance, but also as a statement of goodwill, expressed with the necessary devotion to truly express the true positions of the counterparty. Within the framework of the above, the aim of our study is to analyze the effects of the financial dimension, which is one of the factors affecting business performance, on organizational citizenship behavior of civic virtue. In this context, our study was designed with the questionnaire method, one of the quantitative research methods. The data obtained in the study has been analyzed with the SPSS-24 package program.